FACTORS INFLUENCING PURCHASE INTENTION ON COSMETIC PRODUCTS OF FEMALE CONSUMERS IN YANGON, MYANMAR - Santhaya Kittikowit; Kittiya Suwanabubpa; Sophat Sithisomwong (Bina Nusantara University, 2018)
Since its economic liberalization in 2012, there has been continuous economic and social development in Myanmar. People, especially city dwellers, are receptive to the foreign and modernized cultures, causing the evolving shift in lifestyle and values. Increase inpurchasing power as a result of higher disposable income including higher personal care and beauty consciousness lead consumers to higher attention to personal care and beauty products. As a result, this industry has been enjoying robust growth. However, most cosmetic products seen in the market are imported from overseas, especially from Thailand. As Yangon is a very promising consumer market, it is consequently rather highly competitive. The researcher was then interested in studying the factors influencing purchase intention of female consumers aged 20-60 years old. The objectives of the study are 1.) to explore the current situation of cosmetic industry in Yangon 2.) to identify factors influencing purchase intention and 3.) to provide recommendations to cosmetics exporters or any interested parties. The research analysis was conducted based on the information from consumer and a business operator interviews as well as the subsequent quantitative data acquired from 315 survey respondents during August -October 2017. According to the research findings, brand, quality and price of a product, including social influence all have influence on purchase intention. Moreover, country of origin also has an influence on perceived quality among consumers. Recommendations based on research result interpretation are to develop value for money products for which quality is the primary focus, to formulate effective branding and marketing strategies deploying social influence as one of the strategic communication channels.